2020
DOI: 10.1109/access.2020.3039111
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm-Shifting From Domain-Driven Data Mining Frameworks to Process-Based Domain-Driven Data Mining-Actionable Knowledge Discovery Framework

Abstract: The success of data mining learned rules highly depends on its actionability: how useful it is to perform suitable actions in any real business environment. To improve rule actionability, different researchers have initially presented various Data Mining (DM) frameworks by focusing on different factors only from the business domain dataset. Afterward, different Domain-Driven Data Mining (D3M) frameworks were introduced by focusing on domain knowledge factors from the context of the overall business environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The case study results were evaluated and validated from different real-life domains scenarios such as engineering, education, and business process domains. Results showed that the actionability of learned rules was improved when considering process relevant factors from the above five perspectives of a business process compared to the rules learned from dataset or domain knowledge [48].…”
Section: Vvijay1 and Msatyanarayana (2012) Proposed An Actionable Ass...mentioning
confidence: 99%
“…The case study results were evaluated and validated from different real-life domains scenarios such as engineering, education, and business process domains. Results showed that the actionability of learned rules was improved when considering process relevant factors from the above five perspectives of a business process compared to the rules learned from dataset or domain knowledge [48].…”
Section: Vvijay1 and Msatyanarayana (2012) Proposed An Actionable Ass...mentioning
confidence: 99%
“…The work mentioned in [12] proposed a domain driven data mining approach for developing an actionable knowledge discovery framework. The primary objective of this research is to enhance the implementation of the learned rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data in healthcare collected from different devices and sensors and their integration has become a challenging issue [32]. Fusion approaches should be capable of dynamically combine data belonging to multiple formats and sources [69]. Although, some fusion approaches have been proposed in the literature to manage continuous streaming data.…”
Section: B Management Of Streaming Datamentioning
confidence: 99%